2019
DOI: 10.1111/eea.12848
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping impacts the host location behaviour and population growth of aphids

Abstract: Increasing intrafield plant diversity has been shown to regulate pest populations in various agroecosystems. Among the suggested mechanisms for this bottom-up pest control, the disruptive crop hypothesis states that herbivores' abilities to locate and colonize their host plants are reduced by the presence of non-host plants. Under laboratory conditions, we evaluated how intercropping wheat and legumes modifies the behaviour of apterous cereal aphids, Sitobion avenae (Fabricius) (Hemiptera: Aphididae), in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…To conclude, our results are in congruence with other studies which collectively demonstrate that intercropping different cover crops can influence the insect diversity during the cropping season [29,34,[36][37][38]43,44] and bridge a few, if not all, insects and their benefits, if any, to the subsequent cash crop [41]. However, it is important to plan and select appropriate cover crops for maximum benefits that are both species-and location-specific.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To conclude, our results are in congruence with other studies which collectively demonstrate that intercropping different cover crops can influence the insect diversity during the cropping season [29,34,[36][37][38]43,44] and bridge a few, if not all, insects and their benefits, if any, to the subsequent cash crop [41]. However, it is important to plan and select appropriate cover crops for maximum benefits that are both species-and location-specific.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, intercropping is known to affect the host location of a suitable plant by the insect pest. For instance, Mansion-Vaquie [34] reported the increased time taken by cereal aphids (Sitobion avenae) to locate wheat plants (Triticum aestivum) in a diversified cropping system than in a monoculture. So, it is possible that herbivore abundance remained constant during the early and the late season in the course of locating and feeding on the appropriate host plant.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CPs can represent an effective strategy to disturb their host plant colonization process 6 at various steps comprising adult migration, landing, settlement and reproduction 7 , 8 . The emission of volatile organic compounds (VOCs) by CPs has been shown to significantly modify host plant location by aphids by repelling them from their host plant 9 and/or by reducing the host plant attractivity by masking its olfactory signature 10 . Several works have demonstrated that using CPs can also impact aphids life history traits and significantly reduce fecundity 11 .…”
Section: Introductionmentioning
confidence: 99%
“…If mechanical weed control is not possible for the intercrop in the same row, spraying is necessary. In addition, certain pests such as pigeons, aphids, pea Sitones, and Mycosphaerella pinodes must still be controlled [20,55,[60][61][62][63][64][65]. This must be done in addition to disease treatments that may be necessary for both species despite the beneficial effect that intercropping has on pathogen dynamics [66].…”
Section: Insufficient Control Of Sanitary Issuesmentioning
confidence: 99%